2016
DOI: 10.1002/mds.26593
|View full text |Cite
|
Sign up to set email alerts
|

GBA Mutations Are Associated With Earlier Onset and Male Sex in Dementia With Lewy Bodies

Abstract: GBA mutations are also an important risk factor for DLB development in the Spanish population, are associated with earlier disease onset, and are more prevalent in men. © 2015 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…These demographic and clinical characteristics in our german DLB cohort are in line with findings from two small DLB cohorts of Ashkenazi Jews ancestry and Spanish origin, in which GBA1 promoted a younger onset and higher prevalence of RBD …”
Section: Discussionsupporting
confidence: 90%
“…These demographic and clinical characteristics in our german DLB cohort are in line with findings from two small DLB cohorts of Ashkenazi Jews ancestry and Spanish origin, in which GBA1 promoted a younger onset and higher prevalence of RBD …”
Section: Discussionsupporting
confidence: 90%
“…Dementia and visual hallucinations are conditions that typically occur in advanced stages, and are possibly related to the presence of Lewy bodies in cortical areas. In fact, autopsies of GBA mutation-carriers revealed a more widespread Lewy body pathology in the neocortex than that of non-carriers [6] and an increased rate of GBA mutations in Parkinson’s disease with dementia and Lewy body disease [37]. On the basis of our results we therefore hypothesize that deleterious GBA variants may lead to a major alteration to the molecular mechanisms involved in α-synuclein clearance.…”
Section: Discussionsupporting
confidence: 52%
“…Male sex may increase the risk of developing PD among patients with Gaucher disease type 1 (62), although larger samples need to be studied. One recent study (63) found that, among those with dementia with Lewy bodies (DLB) both with and without GBA1 mutations, men were overwhelmingly represented in GBA-associated DLB, by a male:female ratio of 9:1; the ratio in DLB subjects without GBA1 mutations was 1.1:1. Also, whereas the sex distribution for many inherited parkinsonisms, including LRRK2 and parkin, does not demonstrate the typical increased frequency in men (56, 64), screens of GBA1 samples suggest that GBA-PD may have a more typical 60:40 male:female predominance (61).…”
Section: Discussionmentioning
confidence: 99%